Influence of the formulated surfactant on the characterization of the base oil - Leng, Lai Yee; Nor Ilia, Anisa; Nour, Abdurahman Hamid (Institute of Physics, 2023)
An emulsion is defined as a phase containing two immiscible liquids consisting of water and oil. In the oil and gas industry, the presence of emulsions results in high costs for pumping equipment, reduced performance and increased corrosion rates in pipelines and other equipment. Numerous studies have been conducted for crude oil emulsions, but are still lacking for emulsions present in base oil. Therefore, the research focuses on characterising the emulsified base oil by comparing the physical and thermophysical properties of the emulsified base oil with and without a formulated surfactant and using the base oil as a control sample to observe the stabilisation of the samples. Physical properties include material composition, particle size and distribution, density, viscosity and shear stress; thermophysical properties include thermal stability. Samples were prepared using a homogeniser (2 hours) followed by ultrasonic treatment (2 hours) with 10 mL of water and 190 mL of base oil at room temperature. About 10 mL of the formulated surfactant was added to characterise the emulsified base oil with surfactant. The samples were further analysed for molecular compounds, particle distribution, physical properties (density and viscosity) and thermal stability using DSC and TGA. The results showed that the emulsified base oil with formulated surfactant has higher viscosity and lower density than the emulsified base oil without formulated surfactant.